Penerapan Terapi Musik Klasik terhadap Penurunan Tanda dan Gejala Halusinasi Pendengaran - Wira Marlinta Ningsi; Novita Anggraini; Bangun Dwi Hardika (Journal of Educational Innovation and Public Health, 2024)
Hallucinations are disorders of human perception that assume something exists that actually does not occur. Auditory hallucinations that are not treated properly can have a negative impact on oneself, others and the environment. One treatment to control hallucinations is classical music therapy which can reduce the symptoms of hallucinations. The aim of this research is to determine the possibility of applying classical music therapy to reduce signs and symptoms of auditory hallucinations using the single group pretest and posttest method of applying music therapy to reduce signs and symptoms of auditory hallucinations. The results of the application of EBP classical music therapy which was carried out for 3 days for 10-15 minutes on respondent I (Mr.A), the signs of hallucinations before music therapy were 12 (100%) after classical music therapy the symptoms decreased. hallucinations 3 (25%), Respondent II (Mr. K) had 12 (100%) signs of symptoms down to 4 (33%), Respondent III (Mrs. %). Based on the application of classical music therapy, it was found that signs of auditory hallucinations decreased in three respondents.